Influência das condições de processamento nas propriedades de madeira plástica com pó de castanha de caju (CCC) - Silva, William Cesar Livramento (2019)
The accumulation of solid waste, especially plastic, which has been decomposed for centuries, forest clearing and the growing demand for wood use are some of the many problems that affect the environment, being the wood plastic composite part of the solution. This type of composite generally uses polyolefins, which are one of the major types of plastics found in landfills, and natural fibers that are cheap, affordable, lightweight, and widely available in Brazil. Taking this information into consideration, this work aimed to characterize the mechanical, morphological, rheological, extract content and water absorption properties of wood plastic composites, based on recycled high density polyethylene (HDPE-r) with cashew nut shell powder (CNSP), as a function of cashew nutshell liquid (CNSL) incorporation and changes in extrusion and injection molding conditions. Wood plastic composites samples with CNSL and CNSP for each processing condition were characterized by differential exploratory calorimetry (DSC), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), density, extract content, water absorption, tensile strength and melt index (MFI). The results indicated that the extrusion with open-system degassing and the holding pressure during injection molding directly influenced the extract content and the rheological properties of the composite. It was found that extrusion of the composite without open-system degassing, followed by injection molding at high holding pressure, resulted in composite melt index values close to the flow values of reference polymer matrix (HDPEad). In addition, it was possible to observe, in a general way, that the elongation at break of the polymeric matrix did not change with the CNSP powder incorporation. These results confirm the action of CNSL, as a natural plasticizing and/or lubricating agent of wood plastic composites. Furthermore, the plasticizing effect of LCC on HDPEad reduced the crystallinity and density of the polymeric matrix, confirming its potential use as a plasticizing and lubricating agent in polyethylene-based matrices.